Schools as Inclusive Education Service Providers: Analysis of Teacher Readiness in Implementing Inclusive Education in Elementary School - Afrida Bupu Wae; Saugadi; Hamna (Program Studi PGSD Universitas Madako Tolitoli, 2026)
Teachers' readiness in implementing inclusive education is not fully optimal, especially in the aspect of practical skills in the classroom. This study uses a qualitative approach with phenomenological design to explore in depth the experiences and perceptions of teachers at SDN 1 Tambun, involving one principal and six teachers through observation, structured interviews, and documentation, with interactive model data analysis (reduction, presentation, verification). The results of the study show that cognitively teachers have a fairly good understanding of the concept of inclusion, the characteristics of students with special needs, and the importance of learning differentiation. In the affective dimension, teachers show a positive attitude, characterized by acceptance without discrimination and equal learning opportunities. Meanwhile, in the psychomotor aspect, implementation skills are in the category of being quite good, but not consistent and optimal in practice. The discussion indicates that there is a gap between conceptual understanding and real implementation. These findings confirm that teacher readiness is multidimensional which takes on an important role in the implementation of inclusive education in schools, with the implication that it is necessary to strengthen practice-based training and systemic support to improve the quality of inclusive learning.